A Review Study of Sat Algorithms: Complete and Incomplete: Exploring the Serial Sat Algorithms and Their Completeness (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In Computer Science, the Boolean Satisfiability Problem (SAT) is the problem of deciding whether there exists a translation that fulfills a given Boolean equation. SAT is one of the principal problems that were demonstrated to be NP-complete, which is additionally central to artificial intelligence, algorithm and hardware design. This paper surveys the primary algorithm called as Serial Sat Algorithms which can complete or incomplete.